The Cdk4-E2f1 pathway regulates early pancreas development by targeting Pdx1(+) progenitors and Ngn3(+) endocrine precursors - Kim, So Yoon (Company of Biologists, 2011)
Cell division and cell differentiation are intricately regulated processes vital to organ development. Cyclin-dependent kinases (Cdks) are master regulators of the cell cycle that orchestrate the cell division and differentiation programs. Cdk1 is essential to drive cell division and is required for the first embryonic divisions, whereas Cdks 2, 4 and 6 are dispensable for organogenesis but vital for tissue-specific cell development. Here, we illustrate an important role for Cdk4 in regulating early pancreas development. Pancreatic development involves extensive morphogenesis, proliferation and differentiation of the epithelium to give rise to the distinct cell lineages of the adult pancreas. The cell cycle molecules that specify lineage commitment within the early pancreas are unknown. We show that Cdk4 and its downstream transcription factor E2f1 regulate mouse pancreas development prior to and during the secondary transition. Cdk4 deficiency reduces embryonic pancreas size owing to impaired mesenchyme development and fewer Pdx1(+) pancreatic progenitor cells. Expression of activated Cdk4(R24C) kinase leads to increased Nkx2.2(+) and Nkx6.1(+) cells and a rise in the number and proliferation of Ngn3(+) endocrine precursors, resulting in expansion of the β cell lineage. We show that E2f1 binds and activates the Ngn3 promoter to modulate Ngn3 expression levels in the embryonic pancreas in a Cdk4-dependent manner. These results suggest that Cdk4 promotes β cell development by directing E2f1-mediated activation of Ngn3 and increasing the pool of endocrine precursors, and identify Cdk4 as an important regulator of early pancreas development that modulates the proliferation potential of pancreatic progenitors and endocrine precursors.